Perspectives of Parents towards the Use of Corporal Punishment for Children (Interdisciplinary Research in Education, 2024)
This article intends to identify the perspectives of parents towards the use of corporal punishment for shaping their children's behaviors. To achieve the objective, this research was guided by interpretive paradigm followed by basic qualitative research design. Only 10 parents were chosen by using purposive sampling method to conduct open-ended interview. Document analysis was also used to gather supplementary information required for the study. The study results reveal that though the corporal punishment is legally banned and has negative consequences on children, parents are continuously using it as a disciplinary method to shape their children's behaviors. Nevertheless, there is an increasing recognition of the limitations of punishment and the long-lasting implications of alternative approaches to making sustainable changes in children's behaviors. Almost all parents believe that punishment should be used to a minimal extent by giving more priority to alternative approaches to modify children’s behaviors.